Biometrics and Reproduction of Redbelly Yellowtail fusilier Caesio cuning (Bloch, 1791) in Guraping Bay, Halmahera Island, Indonesia - Marsaoly, Rafil; Bataragoa, Nego; Rondonuwu, Ari B.; Wantasen, Adnan S.; Rembet, Unstain; Lalita, Jans (Sam Ratulangi University, 2024)
This study aims to analyze the biometrics of yellowtail fish (length-weight relationship, growth patterns, condition factors, length-fecundity relationship) and reproductive aspects (gonadal maturity level, gonadal maturity index, and fecundity). The yellowtail fish sample used in this study was taken from fishermen's catches in April 2023. A total of 73 male individuals 17.0-29.9 cm total length, 62.00-356.00 gram, 77 female individuals 17.5-8 .1 cm total length, weight 69.88-288.00 grams. Male length-weight relationship W= 0.0140L2.9662 R2= 0.9812, isometric growth pattern. Female W= 0.0166L2.9104, R2 = 0.9633, growth pattern isometric. Condition factor 1.00 ± 0.06 for males and 1.00 ± 0.07 for females. Gonadal maturity levels I, II, III, IV and V for both males and females with the number of individuals at TKG I 65, II 26, III 25, IV 24, and V 10 individuals. The gonadal maturity index with the highest average value was 1.08 ± 0.47 at TKG IV. Fecundity ranged from 1.771-68.425 which was calculated on 28 fish samples with a mean ± SD of 20.158 ± 19.110. Biometric relationship with fecundity F = 102.67L0.1955, R² = 0.0789 shows a very weak relationship between length and fecundity. Keywords: Length-weight, condition factor, maturity, gonad index, fecundity. Abstrak Penelitian ini bertujuan untuk menganalisis biometrik ikan ekor kuning (hubungan panjang-berat, pola pertumbuhan, faktor kondisi, hubungan panjang-fekunditas) dan aspek reproduksi (tingkat kematangan gonad, indeks kematangan gonad, dan fekunditas). Sampel ikan ekor kuning yang digunakan dalam penelitian ini diambil dari tangkapan nelayan pada bulan April 2023. Sebanyak 73 individu jantan 17,0-29,9 cm panjang total, 62,00-356,00 gram, 77 individu betina 17,5-8,1 cm panjang total, berat 69,88-288,00 gram. Hubungan panjang-berat jantan W= 0,0140 L 2,9662 R2= 0,9812, pola pertumbuhan isometrik. Betina W= 0,0166L2,9104, R2 = 0,9633, pola pertumbuhan isometrik. Fakotor kondisi 1,00±0,06 untuk jantan dan betina 1,00±0,07. Tingkat kematangan gonad I, II, III, IV dan V baik jantan maupun betina dengan jumlah individu pada TKG I 65, II 26, III 25, IV 24, dan V 10 individu. Indeks kematangan gonad dengan nilai rata-rata tertinggi yaitu 1,08±0,47 pada TKG IV. Fekunditas berkisar pada 1.771-68.425 yang dihitung pada 28 sampel ikan dengan rata-rata ± SD 20.158 ±19.110. Hubungan biometrik dengan fekunditas F = 102,67L0,1955, R² = 0,0789 menunjukkan hubungan yang sangat lemah antara panjang dan fekunditas. Kata Kunci: Panjang-berat, faktor kondisi, kematangan gonad indeks, fekunditas.